2015
DOI: 10.1002/mus.24704
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Krebs cycle enzymes in mdx mice

Abstract: This study showed increased activity of Krebs cycle enzymes in cortex, quadriceps, and diaphragm in mdx mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(33 reference statements)
0
7
1
Order By: Relevance
“…Metabolic reprogramming in mdx and DMD muscle is complex, and likely temporally regulated in dynamic fashion. Indeed, contrary to our observation, a recent report revealed elevated activity in oxidative enzymes of the Krebs cycle in mdx diaphragm [ 44 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Metabolic reprogramming in mdx and DMD muscle is complex, and likely temporally regulated in dynamic fashion. Indeed, contrary to our observation, a recent report revealed elevated activity in oxidative enzymes of the Krebs cycle in mdx diaphragm [ 44 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This deficit likely arises in part due to increased intracellular calcium [ 76 ] and muscle regeneration, resulting in an increased need for ATP production via the TCA cycle [ 77 ]. Furthermore, an increase in the activity of TCA cycle enzymes was observed in several brain and muscle tissues of the mdx mouse, suggesting that mitochondrial dysfunction and oxidative stress are part of mdx pathophysiology [ 78 ]. Additional evidence is needed to evaluate whether there is a delay in the onset of oxidative stress and muscle wasting in the slow-progressing dogs compared to fast-progressing dogs.…”
Section: Discussionmentioning
confidence: 99%
“…19,41 Moreover, increased oxidative stress is characteristic of dystrophic muscle. 49,50 We found that mdx-Mss51 KO limb muscle has increased respiration capacity compared to mdx muscle. One possible explanation for the high oxidative capacity in muscle mitochondria from mdx-Mss51 KO mice is that Mss51, acting within the myostatin pathway, could act as a mediator between energy metabolism and endurance capacity in skeletal muscle.…”
Section: Discussionmentioning
confidence: 76%